The Role of Accounting in the Reduction of Money Laundering Operations - Current Practice: An Empirical Study in the Kingdom of Saudi Arabia - Al-Saad, Saleh bin Abdul Rahman; Al- Amoudi, Khadija Mohammed (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aims to shed lights on the extent of adherence by Saudi banks to Anti- Money Laundering standards and procedures, and by identifying the extent to which bank employees are aware of red- flag activities and suspicious indicators of money laundering. Furthermore, the study aims to identify the level of effectiveness of accounting procedures and internal controls in regard to preventing and deterring money laundering. This study employs the extrapolation approach. A questionnaire was distributed to bank employees working in Saudi banks. A total of (48) questionnaires were distributed, (36) questionnaires were suitable for analysis.A number of findings have been reached. The most important findings include: first, the significance of adherence by banks to the policies and procedures issued by the Saudi Arabian Monetary Authority. Second, the significance of awareness by Saudi bank employees of the money laundering activities and the procedures to combat them. Third, the direct or indirect contribution of accounting procedures in preventing and combating money laundering through the use of modern accounting systems, financial reports & statements, letters of credit, and accounting books. Fourth, bank employees exhibit high levels of awareness of the money laundering activities and methods of detecting and preventing them. Finally, it has been found that banks implement a number of accounting procedures, and develop internal controls that assist in combating money laundering activities.
Keywords: money laundering; combating money laundering; accounting system; accounting procedures